Malignant Lymphoma in the Psoas Major Muscle - Nobuhiro Akuzawa; Takashi Hatori; Aya Takase; Jun Aoki; Shinji Sakurai; Masahiko Kurabayashi (Case Reports in Hematology)
An 84-year-old Japanese man taking warfarin to prevent cerebral infarction secondary to atrial fibrillation was admitted to our hospital for evaluation of a painless right back mass. Magnetic resonance imaging (MRI) showed an oval-shaped mass in the right psoas major muscle. The mass showed high intensity on T1-, T2-, and diffusion-weighted imaging and mimicked an acute-phase hematoma. However, it showed no chronological changes typical of a hematoma, and MRI revealed enlargement of the mass 1 week after admission. Histopathological examination of a biopsy specimen revealed diffuse large B-cell lymphoma (DLBCL). Although skeletal muscle lymphoma is rare, physicians should be familiar with its MRI characteristics. In addition, determination of the lymphoma subtype has important implications for the treatment of skeletal muscle lymphoma because DLCBL may have an especially poor prognosis.